Odpowiedzi

Najlepsza Odpowiedź!
2009-12-30T10:40:19+01:00
A) x=y
5x-y=4

x=y
5y-y=4

x=y
4y=4/:4

x=y
y=1

x=1
y=1

b) y=2x+1
4x+y=13

y=2x+1
4x+(2x+1)=13

y=2x+1
4x+2x+1=13

y=2x+1
6x=13-1

y=2x+1
6x=12/:6

y=2x+1
x=2

y=2*2+1
x=2

x=2
y=5

c) 5y-x=3
x=3-y

5y -(3-y)=3
x=3-y

5y-3-y=3
x=3-y

4y=3+3
x=3-y

4y=6/:4
x=3-y

y=6/4
x=3-6/4

x=6/4
y=6/4
2009-12-30T10:41:20+01:00
X=y
5x-y=4
x=y
5y-y=4
x=y
4y=4\:4
x=y
y=1


y=2x+1
4x+y=13
y=2x+1
4x+2x+1=13
y=2x+1
6x+1=13
y=2x+1
6x=12\:6
y=2x+1
x=2
y=4+1
x=2
y=5



2009-12-30T10:43:40+01:00
1, x=y
5x -y = 4
5y-y=4
4y=4/4
y=1


2,b) y=2x+1
4x+y=13
4x+2x+1=13
6x+1=13
6x=13-1
6x=12/6
x=2
y= 2*2+1=5


3
5y-x=3
x=3-y
5y-(3-y)=3
5y-3+y=3
6y=6/6
y=1
x=3-1=2